2005
DOI: 10.1590/s0103-64402005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness of resin-based materials polymerized with LED and halogen curing units

Abstract: The purpose of this study was to evaluate the microhardness of resin-based materials polymerized with a LED (light-emitting diode) light-curing unit (LCU) and a halogen LCU. Twenty cylindrical specimens (3.0 mm in diameter and 2.0 mm high) were prepared for each tested material (Z100, Definite and Dyract). Specimens were light-cured with two LCUs (Ultraled and Curing Light 2500) for either 40 or 60 s on their top surfaces. Hardness was measured on top and bottom surfaces of each specimen. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
(25 reference statements)
2
15
0
2
Order By: Relevance
“…Therefore, this high-density network of organic matrix together with the presence of hard-glass fillers yielding a hard structure may result into superior surface hardness of the ormocer composite 8 . This is almost in agreement with Cefaly's study found that Definite-ormocer was significantly hard, but in contradiction with the finding of Manhart 37,38 . On the other hand, the nanohybrid Tetric Evoceram composite presented the less hard material compared to Filtek ® P90 and Definite.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, this high-density network of organic matrix together with the presence of hard-glass fillers yielding a hard structure may result into superior surface hardness of the ormocer composite 8 . This is almost in agreement with Cefaly's study found that Definite-ormocer was significantly hard, but in contradiction with the finding of Manhart 37,38 . On the other hand, the nanohybrid Tetric Evoceram composite presented the less hard material compared to Filtek ® P90 and Definite.…”
Section: Discussionsupporting
confidence: 88%
“…Não havendo, assim, praticamente nenhuma interferência na transmissão de luz, a qual atinge a área superficial com a maior intensidade possível. Entretanto, para o fundo (base), a luz primeiramente atravessa todo o corpo da resina composta e sendo, então, parte absorvida ou refletida; atenuando a intensidade e reduzindo a efetividade de fotoativação e consequente polimerização nas porções mais profundas do material acarretando, assim, um menor valor de microdureza Vickers [18][19][20][21] . Os valores de microdureza obtidos por um material resinoso são influenciados pelo grau de conversão dos monômeros em polímeros, mas também pela composição da matriz orgânica, pelo tipo, pelo volume e percentual das partículas de carga 6.22 .…”
Section: Resultsunclassified
“…Os testes de microdureza têm sido utilizados em vários estudos como um método viável para avaliar a relativa profundidade de polimerização das resinas compostas e conseqüentemente a eficiência da fonte de luz [5,11,2,23] . Portanto, neste estudo, a microdureza foi usada como um mensurador indireto da profundidade de polimerização da resina composta utilizada.…”
Section: Fibra óPtica Polímerounclassified